1986
DOI: 10.1111/j.1752-1688.1986.tb01892.x
|View full text |Cite
|
Sign up to set email alerts
|

STREAM IMPROVEMENTS AND FISH RESPONSE: A BIO‐ENGINEERING ASSESSMENT1

Abstract: Human modifications of natural streams in the name of habitat improvement take various forms, and the impacts of those improvements, both positive and negative, vary by orders of magnitude from stream to stream. The positive impacts are achieved through careful and timely planning, design, installation and monitoring of projects. Negative impacts are the results of rush jobs dictated by available money, a lack of consideration for limiting factors, untrained and inexperienced personnel, force‐fitting structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…These actions are best carried out through a formally planned project, with multiple objectives (Gardiner 1991) and directed by multidisciplinary teams using a bioengineering assessment (Orsborn and Anderson 1986). Firstly, an evaluation of fish populations and their habitat should be done, taking into account the five main components of fish habitat, namely: spawning areas, food-production areas, refuge zones, flow regimes and water quality (Garcı´a de Jalo´n 1995).…”
Section: Discussionmentioning
confidence: 99%
“…These actions are best carried out through a formally planned project, with multiple objectives (Gardiner 1991) and directed by multidisciplinary teams using a bioengineering assessment (Orsborn and Anderson 1986). Firstly, an evaluation of fish populations and their habitat should be done, taking into account the five main components of fish habitat, namely: spawning areas, food-production areas, refuge zones, flow regimes and water quality (Garcı´a de Jalo´n 1995).…”
Section: Discussionmentioning
confidence: 99%
“…White and Brynildson (1967) stressed that planning for stream improvement projects must consider how the whole stream functions. Platts and Rinne (1985) decried a lack of long‐term scientific research on stream improvement from a watershed standpoint, and Orsborn and Anderson (1986) called for an integrated, bioengineering approach to project planning. More recently, Stroud (1992), Beschta et al (1994), and have suggested a watershed‐oriented approach with emphasis on correcting abusive land‐use practices rather than resorting to instream structures.…”
Section: Discussionmentioning
confidence: 99%
“…Research has focused on selected environmental factors affecting riparian ecosystems, and management methods have evolved from this research which emphasize that single dimension focus. Moreover, this single-dimension perspective has extended to the implementation and planning aspects of stream management (Orsborn and Anderson 1986). Our research indicates that practical determinations of stream corridor widths can be efficiently and easily made using a simple field survey of select reaches of a stream system combined with an analysis of soils, vegetation, physiography, and land-use characteristics.…”
Section: Discussionmentioning
confidence: 98%